Osteocalcin levels in gingival crevicular fluid periodontitis patient with and without type 2 Diabetes Mellitus - Wildan, Muhammad Nabeel; Syaify, Ahmad; Herawati, Dahlia (Odonto : Dental Journal, 2023)
Background: Diabetes Mellitus (DM) is a systemic disease with a high prevalence in Indonesia. Periodontitis is a complication of DM with frequent occurrences. Periodontitis with DM causes greater bone damage than non-DM periodontitis because its conditions can affect osteoblast and osteoclast activity. Osteocalcin (OC), mostly synthesized by osteoblasts, regulates the activity of bone formation and turnover so that it can be a marker of bone formation and turnover to see the severity of the disease. OC can be found in gingival crevicular fluid (GCF). This study aimed to determine osteocalcin levels in gingival crevicular fluid periodontitis patients with uncontrolled type 2 Diabetes Mellitus and non-Diabetes Mellitus.Method: Samples used in this study were gingival crevicular fluid taken from 20 samples of periodontitis patients with DM type 2 (DMT2P) and 20 samples of periodontitis non-DM patients. The OC levels were analyzed using ELISA Kit Osteocalcin then statistical tests were carried out.Result: The results showed that the OC level of the DMT2P group was 0.369 Â± 0.140 while the periodontitis non-DM group was 0.664 Â± 0.141.Conclusion: The OC levels of periodontitis patients with DM are lower than periodontitis patients non-DM.